Technology, outsourcing, and the demand for heterogeneous labor: Exploring the industry dimension - Ljubica Nedelkoska; Simon Wiederhold (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
It has become common within the literature of skill-biased technological change to look at technologies, as well as their impact on the demand for labor as homogeneous across industries. This paper challenges this view. Using a linked employer-employee panel of Germany differentiated by industries for the period 2001-2005, we investigate substitution effects between labor of different skills (tasks) on the one hand, and technology as well as outsourcing on the other. Our findings are at odds with the idea of economy-wide homogeneity of substitution patterns. We find that in some industries IT capital substitutes for labor, while it complements it in others. However, substitution patterns are symmetric across labor types. Outsourcing often correlates negatively with the demand for labor performing explicit and problem-solving tasks. It is mainly uncorrelated or positively correlated with the demand for labor performing interactive tasks. The outsourcing-related results support the offshoring theory proposed by Blinder (2006).
Keywords: J23; J24; O33; 330; demand for skills; technology; outsourcing; Arbeitsnachfrage; Qualifikation; Technischer Fortschritt; Outsourcing; Verarbeitendes Gewerbe; Schätzung; Deutschland